Compositional Analysis of Avocado Pulp: A Product of the Dhankuta Multiple Campus, Tribhuvan University, Dhankuta, Nepal (Orchid Academia Siraha, 2024)
One of the most popular tropical fruits is the avocado, or Persea americana, because of its high nutritional value and adaptability. The Hass kind of avocado is the most widely used cultivar worldwide. Recently, it has gained the attention of consumers, researchers, and farmers being enriched with a high nutritive profile, bioactive compounds, and phytochemicals. In the present study, the chemical composition of the edible part of Avocado fruit (pulp) cultivated in Dhankuta Municipality, Nepal was analyzed using Atomic Absorption Spectroscopy (AAS). The proximate analysis of the fruit was conducted by determining different constituents like moisture, carbohydrate, fat, fiber protein, lipid, and ash content. The tested sample of Avocado fruit contained moisture (76.4%), crude fiber (9.19%), fat (7 %), protein (1.7%), and carbohydrate (4.75%) along with an energy value of 88.87 Kcal per 100g of fruit. The high water and fiber content and low fat and carbohydrate profile signify the implication of Avocado fruit as a healthier fruit in the human diet to achieve more health benefits. Further research on the nutritive value and health benefits of avocado fruit must be encouraged to improve the health status of consumers.